DISEÑO DE ESTRATEGIA DIDÁCTICA PARA MEJORAR EL LENGUAJE ORAL EN ESTUDIANTES DE PRIMER AÑO DE PREPARATORIA DE LA ESCUELA DE EDUCACIÓN BÁSICA “ÁNGEL VILLAMARÍN ORTIZ”, EN EL AÑO LECTIVO DE 2023-2024. - ING. HIDALGO BAJAÑA NASLY MARIELA (2025)
This study aims to design didactic strategies to improve oral language development among first-year students in the preparatory level at "Ángel Villamarín Ortiz" Elementary School, located in the rural area of Isla Bejucal, Baba canton, Los Ríos province (Ecuador). The research identifies significant oral language difficulties that affect students’ academic performance and social integration. A mixed-method approach and intrinsic case study design were applied. Tools such as observation checklists and structured surveys were used, with quantitative data analyzed through SPSS using techniques like Cronbach’s alpha to ensure reliability. The results highlight notable variability in students' language development, guiding the proposal of specific strategies. These didactic strategies are intended to improve oral communication skills, foster meaningful learning, and promote inclusive education from the early stages of schooling.